2003
DOI: 10.1128/iai.71.7.3885-3893.2003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression in Ceca ofHelicobacter hepaticus-Infected A/JCr Mice before and after Development of Typhlitis

Abstract: The inflammatory bowel diseases, Crohn's disease and ulcerative colitis, are chronic inflammatory disorders of the gastrointestinal tract. The causes of these diseases remain unknown; however, prevailing theories suggest that chronic intestinal inflammation results from a dysregulated immune response to ubiquitous bacterial antigens. While a substantial body of data has been amassed describing the role of the adaptive immune system in perpetuating and sustaining inflammation, very little is known about the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…Moreover, this pathogen may cause intestinal disease and gallstones in immunocompetent mice such as C57BL/6 and A/JCr [19,21,23,35]. Mice are usually infected with H. hepaticus through fecal-oral contact, and transplacental infection can occur in immunodeficient mice [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this pathogen may cause intestinal disease and gallstones in immunocompetent mice such as C57BL/6 and A/JCr [19,21,23,35]. Mice are usually infected with H. hepaticus through fecal-oral contact, and transplacental infection can occur in immunodeficient mice [18].…”
Section: Introductionmentioning
confidence: 99%
“…© 2004 American Association for Cancer cancerres.aacrjournals.org Downloaded from 56). Colonization with H. hepaticus in A/JCr mice induces oxidative DNA damage in the liver and the expression of a subset of immunerelated genes, including ␄-IFN in cecal epithelium (57)(58)(59). H. pylori induces H 2 O 2 production and cyclooxygenase-2 expression in gastric epithelial cells (60).…”
Section: Ileal and Colonic Cancer In Gpx-dko Micementioning
confidence: 99%
“…However, the expression of the acute phase protein, ApoH, sometimes is upregulated and sometimes is down regulated, reflecting its pleiotropic functions Then, it become difficult to classify this APP as positive or negative. Indeed, divers data are sometime contradictory such as the observation of ApoH reduction in CSF during cerebral malaria (Agar et al, 2011) and the increase of ApoH in several other infectious diseases (Gast et al, 2006;Myles et al, 2003;van Hemert et al, 2006). Due to different results presented here, ApoH can be considered as one of the major elements of the first line of the innate immune response regulating homeostasis.…”
Section: Apoh and Physiologymentioning
confidence: 68%
“…In a rare clinical case showing that a purpura fulminans phenomenon following an infection with Haemophilus influenzae in an adult was associated to a drastic elevation of the ApoH plasma concentration (Gast et al, 2006). A gene expression study performed on Helicobacter hepaticus-infected mice showed an increased expression of the gene of ApoH three months after infection, once a chronic inflammation was established (Myles et al, 2003). The infection of chickens with Salmonella leads to high ApoH gene over-expression approximately 40-fold excess as compared with uninfected controls (van Hemert et al, 2006).…”
Section: Sacharomyces Cerevisiae Ndmentioning
confidence: 99%